2015
DOI: 10.1371/journal.pone.0145450
|View full text |Cite
|
Sign up to set email alerts
|

Emotions in Everyday Life

Abstract: Despite decades of research establishing the causes and consequences of emotions in the laboratory, we know surprisingly little about emotions in everyday life. We developed a smartphone application that monitored real-time emotions of an exceptionally large (N = 11,000+) and heterogeneous participants sample. People’s everyday life seems profoundly emotional: participants experienced at least one emotion 90% of the time. The most frequent emotion was joy, followed by love and anxiety. People experienced posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
150
3
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(196 citation statements)
references
References 42 publications
22
150
3
1
Order By: Relevance
“…According to Oatley and Johnson-Laird (1996), people react to events by making multiple cognitive evaluations, which may, in turn, elicit different emotional reactions simultaneously or in rapid alternation. This would be in agreement with the literature that has shown the existence of mixed emotions, even when these are opposite in valence (Berrios, Totterdell, & Kellett, 2015;Larsen & McGraw, 2014;Trampe, Quoidbach, & Taquet, 2015). Of note, it has been demonstrated recently that these emotionally ambivalent states can be captured by people's ratings of emotionally charged words (Briesemeister, Kuchinke, & Jacobs, 2012).…”
Section: Distribution Of Words Among the Five Discrete Emotionssupporting
confidence: 92%
“…According to Oatley and Johnson-Laird (1996), people react to events by making multiple cognitive evaluations, which may, in turn, elicit different emotional reactions simultaneously or in rapid alternation. This would be in agreement with the literature that has shown the existence of mixed emotions, even when these are opposite in valence (Berrios, Totterdell, & Kellett, 2015;Larsen & McGraw, 2014;Trampe, Quoidbach, & Taquet, 2015). Of note, it has been demonstrated recently that these emotionally ambivalent states can be captured by people's ratings of emotionally charged words (Briesemeister, Kuchinke, & Jacobs, 2012).…”
Section: Distribution Of Words Among the Five Discrete Emotionssupporting
confidence: 92%
“…The fact that we only studied high school studnets may limit the generalizability of our findings. However, that Trampe et al (2015) found similarly frequent co-occurrences between mixed-valence emotions in their more diverse sample suggests that our findings might be relevant beyond the school context.…”
Section: Discussionsupporting
confidence: 49%
“…Based on results of Study 1 and previous findings by Trampe et al (2015), we expected that positive and negative emotions would occur frequently together, within individuals and situations.…”
Section: Research Questionsmentioning
confidence: 92%
“…19, study 3 from ref. 18-were obtained via correspondence with the authors. The first two datasets were each comprised of 40 participants, all recruited in the United States and performing the study in English.…”
Section: Methodsmentioning
confidence: 99%
“…Studies 1-3 measured the actual rates of transitions between emotions using existing experience-sampling datasets (18,19). These data served as the "ground truth" against which we could test the accuracy of people's mental models.…”
mentioning
confidence: 99%